Treaty interpretation by the iacthr and the ecthr: unity or fragmentation of public international law - Akkuş, Berkant (Ankara: Gazi Kitabevi, 2022)
The rise of increasingly specialised and independent rules, ruling bodies, institutions and branches of the legal profession has led the global trend towards fragmentation. Cases where general international law was previously applied saw the emergence of narrower branches of the law. Trade law, human rights law and environmental law are but a few examples of this trend.
1
Keywords: Sosyal bilimler, -- Hukuk ve genel konular; Social sciences, -- Law and general issues